Esoteris Pendidikan Islam Pada Karomah Syeikh Abdul Qadir Jailani - Ngatoillah Linnaja; Robingun Suyud El Syam (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
One of the most popular Sufi figures in the world is Sheikh Abdul Qadir al-Jailani, due to the height of his knowledge in various fields, as well as his outstanding karomah. So it is necessary to study his karomah, so that there is no cult of individual. This research aims to show elements of novelty, and analyze the esoteric Islamic education at the karamah of Shaikh Abdul Qadir Jailani, which has not been found in previous studies. Through a literature study using a phenomenological approach, the finding was that the karomah of Sheikh Abdul Qadir al-Jailani was only positioned as a reinforcement of the essence of Islamic teachings where the dimensions of the two pillars, namely monotheism and fiqh, must run side by side. The position of his guardianship must be placed in the aspect of understanding that everything is God's will. The implication of the research is that external reasoning is needed to understand the Shari'a and internal reasoning to see the essence of religion, including karomah aulia. The research is expected to contribute to the development of Islamic thought in Sufistic aspects.